(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2024)
The accounting guide is the basic pillar of all accounting systems. It is like a lighting lamp that works to guide professional accountants so that they can complete the tasks entrusted to them, including accounting procedures and treatments. We can infer the content of the third pillar of the pillars and components of the unified accounting system through its title, as the word (guide) ) gives a clear meaning to what is contained in this guide, which will serve as a guide or indicator through which we can be guided towards carrying out specific tasks, and its association with the word (accounting) becomes more indicative that it will be a digital guide that guides those who use it, towards better and optimal performance, The research aims to propose an accounting guide for the oil and gas industry in Iraqi oil units in accordance with International Financial Reporting Standards (IFRSs) and International Accounting Standards (IASs) with completely new numbers and names, except for those that were derived from the unified accounting system currently applied in Iraqi oil units, which are appropriate. And the nature of activity in Iraqi oil companies, as this is considered the main objective of the research. To achieve the objectives of the research and answer its questions, the researchers followed the deductive approach by referring to possible sources such as official documents, university theses, periodicals, research and books related to the subject, as well as websites related to the subject of the research on the Internet. And using the inductive and analytical approach to complete the applied aspect through the existing accounting guide in the unified accounting system currently applied in the oil and gas industry in Iraq and identifying its weak points, and proposing a new accounting guide in accordance with the International Financial Reporting Standards (IFRSs) and International Accounting Standards (IASs) that suits the nature of the industry. Oil and gas in Iraq.. The researchers reached many conclusions, the most important of which is that there is a clear change in the numbers and names of accounts that must appear in the accounting manual in order to be compatible with the International Financial Reporting Standards (IFRSs) and the International Accounting Standards (IASs). The researchers recommended that Iraqi oil units adopt the use of this new proposed guide, which could be more suitable for the oil and gas industry and prepared in accordance with International Financial Reporting Standards (IFRSs) and International Accounting Standards (IASs).